2006
DOI: 10.1111/j.1475-097x.2006.00676.x
|View full text |Cite
|
Sign up to set email alerts
|

Further insights into the role of angiotensin II in kidney development

Abstract: Over the past decade, compelling studies have highlighted the fundamental role of the renin-angiotensin system (RAS) in renal development and long-term control of renal function and arterial pressure. The present review provides an update of the understanding of how the RAS controls nephrogenesis and nephrovascular development. In addition, the investigations linking the perinatal development of RAS inhibition-induced renal dysmorphology and establishment of adult blood pressure are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 89 publications
(159 reference statements)
0
19
1
Order By: Relevance
“…Although the link between developmental nephron deficit and impaired sodium excretory capacity remains unclear, it is likely due to more than simply reduced glomerulus number and may also include alterations in renovascular and tubular morphology, along with disrupted tubular sodium transporter expression. 6 Despite the compelling findings in the present study by Salazar et al, 9 much remains unclear regarding the potential renoprotective effects of sex or sex hormones in this model of hypertension.…”
contrasting
confidence: 38%
See 1 more Smart Citation
“…Although the link between developmental nephron deficit and impaired sodium excretory capacity remains unclear, it is likely due to more than simply reduced glomerulus number and may also include alterations in renovascular and tubular morphology, along with disrupted tubular sodium transporter expression. 6 Despite the compelling findings in the present study by Salazar et al, 9 much remains unclear regarding the potential renoprotective effects of sex or sex hormones in this model of hypertension.…”
contrasting
confidence: 38%
“…1,2,5 Although it has long been observed that a variety of endocrine and nutritional insults during renal development result in developmental deficits in the kidney (reviewed elsewhere 1 ), abnormalities in the RAS appear to be a central common pathway. 6 The importance of the intrarenal RAS in renal development has been recognized for over a decade, when initial studies, such as those by Friberg et al, 7 recognized that angiotensin II type 1 (AT 1 ) receptor antagonism during nephrogenesis leads to development deficits in the kidney. Hence, experimental studies using AT 1 receptor antagonism during renal organogenesis provide a robust model for interrogation of the mechanisms underlying these developmental deficits in renal function.…”
mentioning
confidence: 99%
“…During kidney development, angiotensin II (Ang II), a biologically and physiologically active peptide, functions through its two major receptors, Ang II type 1 and Ang II type 2 receptors (AT 1 R and AT 2 R) [3][4][5][6]. AT 1 R and AT 2 R belong to the large family of G protein-coupled receptors with seven transmembrane domains and are both expressed in the fetal kidney [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Independent roles of the local RAS in developing kidney have also been indicated (Esther et al, 1997;Norwood et al, 2000). The mechanisms by which Ang II mediates tubulogenesis and nephrovascular development have been recently clarified and reviewed in detail (Yosypiv and El-Dahr, 2005;Lasaitiene et al, 2006).…”
Section: Renal Development and Agingmentioning
confidence: 99%